Pemanfaatan Blockchain pada Pembangunan Sistem Informasi Pembiayaan Usaha Mikro Kecil Menengah - Asep Id Hadiana; Yudi Setiadi Permana; Eddie Krishna Putra (Ikatan Ahli Informatika Indonesia, 2019)
Technological developments are happening very rapidly, more and more new technologies are emerging. Today, technology is dominated by a centralized system. New technology that is quite interesting to study, one of which is Blockchain. Blockchain is a distributed ledger technology that enables direct (peer-to-peer) transactions without the need to involve trusted third parties. Micro, small and medium enterprises (MSME) are one of the supporting factors for economic development in Indonesia. For now, many MSME activities use digital media such as the internet using facilities like e-commerce or market places. In developing for business, MSME need capital for MSME operational activities can run. In this case, support from financial institutions is needed such as banking, investors or other funding sources. However, to be able to access financing from these parties, requirements and bureaucracy are quite difficult. The purpose of this study is to create a system that can make it easier for MSME to get financing with easy terms with easy bureaucracy as well. This system is supported by Blockchain technology to store transaction data where security and authenticity of the data can be guaranteed, and provide transparency of the financing process to all relevant parties.